Determination of optimal conditions of action of beta-galactosidases of producers with different properties - M. A. Shpak; S. A. Ryabtseva; A. D. Lodygin; P. I. Kornienko; P. S. Kolyadina (Современная наука и инновации)
The synthesis of beta-galactosidase is observed in microorganisms of various taxonomic groups, including some strains of yeast fungi and lactic acid bacteria. The present work considers the study of optimal conditions of beta-galactosidase activity obtained as a result of separate and co-cultivation of domestic yeast strains Kluyveromyces marxianus Y-1338, Kluyveromyces lactis Y-1333, Kluyveromyces lactis Y-1339 and starter cultures Lactobacillus acidophilus, Streptococcus thermophilus. Studies of the pH and temperature effect on the activity of yeast and lactic acid bacteria enzymes received as a result of their separate and co-cultivation were carried out in the work. It has been established that the optimum of the enzyme activity depends primarily on the type of its producer. In the case of separate cultivation, the maximum activity of yeast beta-galactosidases was observed for the species K. lactis and was 4 times higher than K. marxianus. Moreover, for the K. lactis Y-1333 and K. lactis Y-1339 strains, similar results and optimal conditions were found at pH 5.0 and temperature 60°C. In experiments with lactic acid bacteria, the activity of beta-galactosidase of acidophilic bacillus was twice higher than the thermophilic streptococcus enzyme activity, had greater resistance to temperatures and stability over almost the entire pH range. Maximum lactase activity of Lb. acidophilus B was observed at 60°C and pH 5.0, and St. thermophilus B at 40° C and pH 5.0. It was found that the activity of combined enzymes of yeast and lactic acid microorganisms was significantly higher than the activity of beta-galactosidase after their separate cultivation. The maximum lactase activity of K. marxianus Y-1333 + St. thermophilus B was higher by 45% than K. marxianus Y-1333 and almost 3 times higher than value of St. thermophilus B. The greatest activity (~1.42 IU/cm3 ) was obtained for the combination of K. lactis Y-1333 + Lb. acidophilus B. In the case of beta-galactosidases obtained by co-cultivation of yeast and viscous cultures of lactic acid microorganisms, optimal conditions include pH 5.0 and 60°C for the combination of cultures K. lactis Y-1333 + St. thermophilus B and K. lactis Y-1339 + St. thermophilus B, pH 7,0÷7,5 and 60°C for K. lactis Y-1333 + Lb. acidophilus B, pH 6,0÷6,6 and 60°C using the enzyme K. marxianus Y-1338 + Lb. acidophilus B.